Using Continuous Glucose Monitoring as a Biological Feedback Strategy to Motivate Physical Activity in Cancer Survivors: A Mixed-Methods Pilot Study - Yue Liao PhD; Grace E. Brannon PhD; Chad D. Rethorst MA; Miranda Baum MD; Therese B. Bevers PhD; Susan M. Schembre PhD, MPH; Karen M. Basen-Engquist PhD (Cancer Control, 2025)
Introduction Identifying novel strategies to motivate regular physical activity in cancer survivors continues to be a critical mission, as the majority of cancer survivors are not sufficiently active to achieve the many health benefits of being regularly physically active. Providing biological feedback is one of the behavioral change techniques that shows promising effects in physical activity interventions. This study used a mixed-methods approach to test the acceptability and changes in physical activity motivation of a pilot intervention that provided personalized feedback via text messaging based on data from an activity tracker (Fitbit) and continuous glucose monitor (CGM) over a 4-week period. Methods Twelve breast and colorectal cancer survivors completed this pilot intervention, which involved a one-on-one educational session followed by a 4-week intervention period with a Fitbit wristband and CGM. They received 2-3 weekly text messages based on their Fitbit and CGM data that aimed to increase their motivation to engage in physical activity. Participants completed surveys assessing motivational readiness before and after the intervention, and a post-intervention survey that assessed acceptability of the intervention. Exit interview was also conducted to collect their feedback and opinions toward the intervention. Results Both quantitative and qualitative results suggest a high acceptability of the study devices (ie, Fitbit and CGM) as well as the intervention components (e.g., the glucose-based biological feedback). Participants reported a significant decrease in the preparation stage and an increase in the action and maintenance stages (ps < 0.05). Results from qualitative analysis further indicate participants’ positive changes in physical activity motivations. Conclusion The use of CGM along with an activity tracker is a viable method to provide personally relevant and motivating biological feedback messages to motivate physical activity in cancer survivors. Future studies can incorporate this behavior change technique into their intervention and further evaluate its impact on behavior change and related health outcomes. Clinical trial number: NCT05124405.